2020
DOI: 10.1021/acs.langmuir.0c02329
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Marine Antifouling Coatings Based on a Hydrophilic Polyvinylpyrrolidone and Hydrophobic Fluorine–Silicon-Containing Block Copolymer

Abstract: The development of environmentally friendly and highly efficient antifouling coatings is vastly desirable in the marine industry. Herein, we prepared a novel amphiphilic block copolymer that combined hydrophilic polyvinylpyrrolidone (PVP) with hydrophobic poly(1-(1H,1H,2H,2H-perfluorodecyloxy)-3-(3,6,9-trioxadecyloxy)-propan-2-yl acrylate) (PFA) and polydimethylsiloxane (PDMS). The amphiphilic copolymer (PVP−PFA−PDMS) was blended into a cross-linked PDMS matrix to form a set of controlled surface composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Nevertheless, FR siloxane coatings require improvements to overcome some disadvantages, including the higher fouling accumulation during idle time [ 26 ] and the low fouling release efficacy towards some microalgae diatoms [ 27 ]. As a result, hydrophilic fouling-resistant polymers, including PEG and polyzwitterions, were extensively investigated for the hydrophilization of hydrophobic PDMS-based FR coatings [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. PEG, especially, is considered a “gold standard” in the field of anti-biofouling coatings, even though it was proved to undergo oxidative degradation generating some toxic compounds, including 1,4-dioxane and formaldehyde [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, FR siloxane coatings require improvements to overcome some disadvantages, including the higher fouling accumulation during idle time [ 26 ] and the low fouling release efficacy towards some microalgae diatoms [ 27 ]. As a result, hydrophilic fouling-resistant polymers, including PEG and polyzwitterions, were extensively investigated for the hydrophilization of hydrophobic PDMS-based FR coatings [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. PEG, especially, is considered a “gold standard” in the field of anti-biofouling coatings, even though it was proved to undergo oxidative degradation generating some toxic compounds, including 1,4-dioxane and formaldehyde [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…And then, the polymer-coated wafers were immersed at 37°C in the as-prepared bacterial suspension. Samples were collected from the bacterial suspensions at various time points (1,4,8,16, and 24 h) and were rinsed three times with PBS gently. The taken samples at each point were put in 1 mL sterile PBS, shook for 1 min, sonicated for 15 min, and shook again for 1 min.…”
Section: The Bacterial Adhesion Tendency Of the Polymer Films With Increasing The Exposure Time In A Bacterial Suspensionmentioning
confidence: 99%
“…It has been reported that the air-bubble layer of the superhydrophobic film cannot maintain on the surface for a longer period of time, and bacteria can attach to the superhydrophobic surface with time. [12] (1,4,8,16, and 24 h) after exposure to a bacterial suspension in BHI. Results are expressed as mean ± SD (n = 3).…”
Section: Dynamic Antiadhesion Properties Of Ptfe/pvp and Ptfe/pvp-i Filmsmentioning
confidence: 99%
See 2 more Smart Citations